Investigating Truck Drivers' Behavior Towards Potential and Developing Hazards - M.H. Johari; M.H. Basir; M.K.A. Ibrahim; A.S. Salleh; S. Liew; A. Hamzah (Journal of the Society of Automotive Engineers Malaysia, 2025)
Having attentive drivers is essential to maintaining road safety, especially when it comes to road freight transportation. The hazard perception experiment assesses a person's ability to see the whole road scene, recognize potentially dangerous situations, and respond to them in a way that is appropriate and safe. There is a correlation between a higher collision risk and poor hazard perception, or the inability to recognize potentially hazardous traffic and road conditions. In the effort to improve the current understanding of driver attentiveness will perhaps increase the safety of road freight transportation, this article suggests performing trials. The study intends to ascertain if danger-anticipating skills may be enhanced without explicit teaching by utilizing the repetition effect, which is frequently shown in procedural learning tasks. This research will identify the merits or demerits of an emergency response team's repetitive procedural driving culture, inspired by principles of skill acquisition. In this study, the analysis of driving hazard detection and reaction times reveals significant insights into driver behavior and safety. The study identifies scenarios such as broken-down vehicles and cattle on the roadside as frequently detected hazards, indicating high driver awareness in these situations. Conversely, dynamic scenarios like motorcycles ahead and pedestrians at roundabouts are less often detected, suggesting a need for enhanced driver training and awareness in these contexts. Finally, the significance of this research lies in its exploration of an alternative driving training methodology that is in line with implicit learning principles. This technique may provide truck drivers with a more effective and efficient way to improve their ability to anticipate hazards.